Enhanced multi-mode control of Z-source virtual synchronous generator for photovoltaic systems using fuzzy logic controller - Rafi, Vempalle; Dhal, Pradyumna Kumar; Vali, Shaik Hussain; Krishna, Sadhu Radha; Suryavalli, Uppuluri; Prakash, S. Vinoth John (Institute of Advanced Engineering and Science, 2025)
An enhanced multi-mode control solution for a Z-source virtual synchronous generator (ZVSG) that makes use of a fuzzy logic controller (FLC) is proposed by this study for use in photovoltaic (PV) systems. As a potential grid integration option for PV systems, the ZVSG has great potential due to its steady and adjustable power production. A stable voltage and frequency output can be maintained by the ZVSG when it is running in a variety of modes, such as grid-connected, standalone, and islanding, according to the control approach that has been provided. The FLC is used for the purpose of controlling the switching frequency of the ZVSG as well as the DC-link voltage. The performance of the ZVSG is improved by the FLC-based control approach that has been proposed. This technique reduces the steady state error and offers a rapid dynamic response. The results of the simulation show that the recommendation for a control approach improves the performance of the ZVSG across a wide variety of operating modes and load conditions.